Factors affecting women's waste separation behaviour in Turkey - Güngör Karakaş (CES Working Papers, 2021)
Turkey has recently made some regulations on environmental issues. Perceptions and participation of households are important for the implementation of legal regulations. Since women were more interested in household waste than men, in this study, environmental behaviours of women was investigated in Çorum province. Analysis of women's approach to separation of recyclable wastes in their source were investigated using the Theory of Planned Behaviour (TPB), Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The research was conducted in 2018 with 414 participants. According to the results of the research, it was determined that the most important factor of separation behaviour at source was consequences awareness. It was determined that almost all of the participants were willing to separate the wastes at source if necessary facilities were provided. For this reason, the work should be done to create consequences awareness in the province. Finally, for the sustainable environmental applications, separation facilities must be provided at all locations in the province.
Keywords: 330; Sustainable Environment; Behaviour; Waste; Separation; Women